2021
DOI: 10.1016/j.ssmph.2021.100811
|View full text |Cite
|
Sign up to set email alerts
|

Trends in child marriage and new evidence on the selective impact of changes in age-at-marriage laws on early marriage

Abstract: This study adopts a cohort perspective to explore trends in child marriage – defined as the proportion of girls who entered first union before the age of 18 – and the effectiveness of policy changes aimed at curbing child marriage by increasing the minimum legal age of marriage. We adopt a cross-national perspective comparing six low- and middle-income countries (LMICs) that introduced changes in the minimum age at marriage over the past two decades. These countries belong to three broad regions: Sub-Saharan A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Without effective monitoring and enforcement mechanisms, age-at-marriage laws may have a limited impact on delaying marriage age among girls. 11 Research from Malawi and Nigeria identified the absence of monitoring systems, the lack of efforts to disseminate treaty-monitoring-body recommendations to institutions and individuals who could play a role and insufficient clarity on who is responsible for coordinating implementation. 12 13 Another study in Malawi highlighted the promise of chiefs as cultural intermediaries in child marriage reform, implementing culturally embedded policy change by mobilising democratic and non-democratic powers.…”
Section: Resultsmentioning
confidence: 99%
“…Without effective monitoring and enforcement mechanisms, age-at-marriage laws may have a limited impact on delaying marriage age among girls. 11 Research from Malawi and Nigeria identified the absence of monitoring systems, the lack of efforts to disseminate treaty-monitoring-body recommendations to institutions and individuals who could play a role and insufficient clarity on who is responsible for coordinating implementation. 12 13 Another study in Malawi highlighted the promise of chiefs as cultural intermediaries in child marriage reform, implementing culturally embedded policy change by mobilising democratic and non-democratic powers.…”
Section: Resultsmentioning
confidence: 99%
“…Alternative policies must ensure that girls' future life outcomes, including their participation in higher education and society, are encouraged and protected. 50 In Amhara (Ethiopia), awareness of marriage law enforcement is positively related to supporting girls' rights to choose their age and partner. 51 The role of mass media and social communication can suppress the high rate of child marriage.…”
Section: Dominant Hegemony Receptionmentioning
confidence: 99%
“…She finds that the law reduced adolescent births, child marriage, and sexual debut by age 18 for exposed cohorts of females aged 15-18. Batyra and Pesando (2021) examine laws in six countries and conclude that they are not effective in curbing child marriages. 22 Amirapu et al (2020) find that when parents, especially fathers or elders, were informed of the tougher new minimum age laws in Bangladesh, adolescent marriages increased in the short-term.…”
Section: A2 Demand Sidementioning
confidence: 99%